THICKNESS OPTIMIZATION OF PEROVSKITE SOLAR CELLS USING GPVDM SIMULATION - Yogesh Patel; Sachin Desai; Dr. Uday Trivedi (IJRDO - Journal of Electrical And Electronics Engineering, 2025)
Due to their great potential efficiency and low cost of production, perovskite solar cells have become an attractive technology for next-generation photovoltaics. In this study, we use the modelling tool GPVDM (Generalised Photovoltaic Device Model) to look at how thickness variations affect the performance of perovskite solar cells. By systematically varying the thickness of the perovskite layer and other functional layers, we aim to optimize the device performance. The simulation focuses on key parameters such as absorption efficiency, charge transport characteristics, carrier recombination rates, photocurrent generation, and open-circuit voltage. The perovskite (PVK) absorber layer is composed of CH3NH3PbI3, the hole transport layer is composed of spiro-OMeTAD, and the electron transport layer is composed of TiO2. These layers are sandwiched together to form the simulated solar cell. Solar cells' conversion efficiency can be increased by adjusting the layer thicknesses of various materials. The outcomes show that it is feasible to have layer thicknesses with a maximum power conversion efficiency of 23.32%.